25
$\begingroup$

In calculus, is $ \dfrac{\mathrm{d}{x}}{\mathrm{d}{y}} = \dfrac{1}{\left( \dfrac{\mathrm{d}{y}}{\mathrm{d}{x}} \right)} $? I’m so confused about this matter. What would be a proof of it?

Edit: By the Chain Rule, $ \dfrac{\mathrm{d}{y}}{\mathrm{d}{x}} \cdot \dfrac{\mathrm{d}{x}}{\mathrm{d}{y}} = \dfrac{\mathrm{d}{y}}{\mathrm{d}{y}} = 1 $, so this confuses me.

$\endgroup$
2
  • 3
    $\begingroup$ This is imprecise. What you are asking is: what is $(f^{-1})'$ in terms of $f'$? $\endgroup$
    – wj32
    Feb 2, 2013 at 4:39
  • $\begingroup$ There is nothing confusing in $\frac{dy}{dx}.\frac{dx}{dy}=1$. On the opposite, this is just a confirm that $\frac{dx}{dy}=1/\frac{dy}{dx}$. $\endgroup$
    – user65203
    Feb 6, 2015 at 11:06

2 Answers 2

22
$\begingroup$

The precise statement is as follows.

Let $ I $ be an open interval, and suppose that $ f: I \to \mathbb{R} $ is one-to-one and continuous on $ I $. If $ f $ is differentiable at $ a \in I $ and $ f'(a) \neq 0 $, then $ f^{-1}: f[I] \to I $ is differentiable at $ b = f(a) $ and $$ (f^{-1})'(b) = \frac{1}{f'(a)}. $$

Using Leibniz’s notation, the formula above can be expressed as $$ \frac{dx}{dy} \Bigg|_{y = b} = \frac{1}{\left( \dfrac{dy}{dx} \Bigg|_{x = a} \right)}. $$

$\endgroup$
1
  • 2
    $\begingroup$ An important point is evaluating the derivatives at the correct points as shown here. $\endgroup$ Feb 2, 2013 at 4:48
7
$\begingroup$

If the real variables $x$ and $y$ are dependent functionally on each other, say by the equations $y = f(x)$ and $x = g(y)$, then where things are differentiable, we do indeed have an equation

$$ \frac{dy}{dx} = \frac{1}{\frac{dx}{dy}} $$

and the most straightforward proof is as you indicated by the chain rule:

$$ \frac{dy}{dx} \frac{dx}{dy} = \frac{dy}{dy} = 1$$

and then solving the equation

$$ \frac{dy}{dx} \frac{dx}{dy} = 1$$

for $\frac{dy}{dx}$.

The argument can be rephrased in terms of functions rather than dependent variables: from the identity

$$ x = g(f(x)) $$

we differentiate to obtain

$$ 1 = g'(f(x)) f'(x) $$

and thus the analogous identity

$$ f'(x) = \frac{1}{g'(f(x))} $$


More generally, in the language of differential forms, the expression $\frac{dy}{dx}$ is defined to be the expression satisfying

$$ dy = \frac{dy}{dx} dx $$

if that is possible. When both $\frac{dy}{dx}$ and $\frac{dx}{dy}$ are defined, then we have two equations

$$ dy = \frac{dy}{dx} dx \qquad \qquad dx = \frac{dx}{dy} dy $$

and can substitute to obtain

$$ dy = \frac{dy}{dx} \frac{dx}{dy} dy $$

and so we again have

$$\frac{dy}{dx} = \frac{1}{\frac{dx}{dy}} $$

wherever $dy$ is nonvanishing. An example of a situation where both are defined is if the variables $x$ and $y$ are functionally related by a differentiable equation $f(x,y) = 0$. Taking the differential gives

$$ f_1(x,y) dx + f_2(x,y) dy = 0$$

where $f_1$ is the derivative of the two-variable function $f$ with respect to the first variable. When both $f_1$ and $f_2$ are nonzero, we can solve the equation in both ways to see that both $\frac{dx}{dy}$ and $\frac{dy}{dx}$ are defined.

$\endgroup$
1
  • $\begingroup$ Here is the chain rule explicitly applied to this problem. By definition, $x = f^{-1} ( f(x))$ where the inverse function exists. Differentiating both sides with respect to $x$, $1 = \frac{d f^{-1} (x)}{d f(x)} \frac{d f(x)}{dx}$ and given that $y = f(x), x = f^{-1} (y)$ where $x$ is a dummy variable, $1 = \frac{dx}{dy} \frac{dy}{dx} \implies \frac{dx}{dy} = \frac{1}{\frac{dy}{dx}}$. $\endgroup$
    – Toby Mak
    Jun 6, 2021 at 6:00

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.